ASME 2011 Conference on Smart Materials, Adaptive Structures and Intelligent Systems, Volume 2 2011
DOI: 10.1115/smasis2011-5168
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Flow Sensors Fabricated From Carbon Nanomaterials

Abstract: Carbon-based flow sensors can be made by embedding carbon nanotubes (CNT) into a polymeric substrate. Specifically, when a conductive aqueous solution flows over the surface of the exposed CNT, a flow-dependent voltage is generated. The carbonaceous flow sensors fabricated in our work were all tested in salt water (5% NaCl). In order to measure the surface coverage of the CNT coated sensors, the electrical resistance across the surface of each sample was measured. Electrical Impedance Spectroscopy (EIS) measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In fact, Yu et al [134] has shown that piezoelectric micro-fibers have the potential for use as real-time flow sensors. Research is ongoing for developing higher performance flow sensors and to apply these technologies for various applications [135][136][137].…”
Section: Flow Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Yu et al [134] has shown that piezoelectric micro-fibers have the potential for use as real-time flow sensors. Research is ongoing for developing higher performance flow sensors and to apply these technologies for various applications [135][136][137].…”
Section: Flow Sensingmentioning
confidence: 99%
“…Instead of using pristine nanotubes, Cao et al [141] has verified that flow sensing is possible using SWNT/PDMS composite thin films. Pinto et al [142] has also studied the flow sensing response of PDMS-based films embedded with SWNTs and single-walled nanohorns (SWNH). Electrical impedance spectroscopy has been conducted for characterizing sample response to air and fluid exposure, and small changes in sensor voltage has been measured due to varying flow conditions.…”
Section: Flow Sensingmentioning
confidence: 99%